Algae-biomass for Fuel, Electricity and Agriculture - R., Mamat; Bundschuh, Jochen; Yusaf, Talal; Maity, Jyoti Prakash; Nelson, Emily; Indra Mahlia, T.M. (Elsevier, 2014)
“Modern society continues to rely largely on fossil fuels to preserve economic growth and today's standard of living. However, for the first time, physical limits of the Earth are met in our encounter with finite resources of oil and natural gas and its impact of greenhouse gas emissions onto the global climate. Never before has accurate accounting of our energy dependency been more pertinent to developing public policies for a sustainable development of our society, both in the industrial world and the emerging economies.” Minutes, Debate of Senate (Eerste Kamer), 2009 (in Dutch)1